Monasticism : A Very Short Introduction - Davis, Stephen J. (Great Clarendon Oxford University Press, 2018)
Explores the phenomenon of monasteries from antiquity to present day as cloister places of refuge where fundamental aspects of life are regimented and spirituality is practiced.
Include Illustrations and Index
Keywords: Monasticism and religious orders -- Monastic and religious life